2002
DOI: 10.1677/jme.0.0290023
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of mRNA using real-time reverse transcription PCR (RT-PCR): trends and problems

Abstract: The fluorescence-based real-time reverse transcription PCR (RT-PCR) is widely used for the quantification of steady-state mRNA levels and is a critical tool for basic research, molecular medicine and biotechnology. Assays are easy to perform, capable of high throughput, and can combine high sensitivity with reliable specificity. The technology is evolving rapidly with the introduction of new enzymes, chemistries and instrumentation. However, while real-time RT-PCR addresses many of the difficulties inherent in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
1,702
4
59

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 2,233 publications
(1,783 citation statements)
references
References 88 publications
18
1,702
4
59
Order By: Relevance
“…However, as apparent from Table 1, concentrations of tubulin mRNA measured by quantitative PCR can vary rather widely according to tissue, sex and/or hormonal state (e.g., HYPOX). These findings are in agreement with our [19] as well as other [20,21] earlier reports of significant sex, hormonal and non-hormonal effects on the expression levels of such housekeeping genes as cyclophilin, tyrosine aminotransferase, β-actin, tubulin, glyceraldehyde-3-phosphate dehydrogenase and 18S in rat liver [19]. Accordingly, we normalized real-time PCR determined CYP2C11 mRNA concentrations to total RNA (Table 1) as we [22] and others [23] have reported.…”
Section: Sexually Dimorphic Expression Of Tubulinsupporting
confidence: 93%
“…However, as apparent from Table 1, concentrations of tubulin mRNA measured by quantitative PCR can vary rather widely according to tissue, sex and/or hormonal state (e.g., HYPOX). These findings are in agreement with our [19] as well as other [20,21] earlier reports of significant sex, hormonal and non-hormonal effects on the expression levels of such housekeeping genes as cyclophilin, tyrosine aminotransferase, β-actin, tubulin, glyceraldehyde-3-phosphate dehydrogenase and 18S in rat liver [19]. Accordingly, we normalized real-time PCR determined CYP2C11 mRNA concentrations to total RNA (Table 1) as we [22] and others [23] have reported.…”
Section: Sexually Dimorphic Expression Of Tubulinsupporting
confidence: 93%
“…Normalisation to GAPDH was already reported as valid (Wall and Edwards 2002), however in most cases this gene proved to be inappropriate as endogenous control in quantification assays (Schmittgen and Zakrajsek 2000;Goidin et al 2001;Kim et al 2003). A maximum variability of GAPDH of 25 fold has been reported (Dheda et al 2004), and according to Bustin (2002) for most experimental conditions the use of GAPDH is inappropriate and should be discontinued. Our results support this conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…In many cases genes traditionally chosen for the constancy of their expression have gained this reputation based on assays conducted under a limited number of conditions or with relatively few tissues. Recent data in humans shows considerable variation in expression of certain housekeeping genes in different tissues (Vandesompele et al 2002;Bustin et al 2002). A study of the expression levels of ribosomal RNA 18S, GAPDH, actin and tubulin in rice seedlings subjected to UV-irradiation revealed that only 18S ribosomal RNA was a suitable internal control for real time RT-PCR (Kim et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…qPCR Several different methods of performing qPCR measurements can be used to detect small amounts of RNA or DNA (Bustin, 2002). Using probes that are labeled with both a fluorophore and fluorescence-quenching molecule, amplicon generation can be detected and quantified in real time during a PCR.…”
Section: Cishmentioning
confidence: 99%